GP167 Trends in injury related fatalities in the irish paediatric population: a review of national mortality data. (June 2019) - McGarvey, Cliona; Hamilton, Karina; Matthews, Tom; Devaney, Deirdre; Nicholson, Alf
Abstract : Background: Injury is a leading cause of childhood death throughout the EU. For every fatality many more children are seriously injured and a large proportion left permanently disabled. Age specific, population based data is required to enable accurate assessment of the magnitude and characteristics of the injury problem. Objective: To determine the burden of accident and injury related childhood mortality in Ireland by determining the prevalence and characteristics of intentional and unintentional injury related deaths over a twelve year period from 2006 to 2017. Design: Retrospective review of cause of death information on all deaths <15yrs, registered in Ireland from 2006–2017, with additional detailed information retrieved from autopsy reports reviewed by paediatric pathologists. Results: A total of 4, 443 paediatric deaths (<15yrs) were registered in Ireland during 2006–2017, 49% of which were aged >28 days. Beyond infancy the leading cause of childhood death during this period (26.5%) was accident and injury. Most were unintentional accidents, children 1–4yrs being most susceptible (3.9/100, 000 vs. 2.8/100, 000 1–14yrs). Proportionate injury mortality increased gradually with age ranging from <1% of neonatal deaths to 36% of deaths in children 10–14yrs. Road traffic accidents (RTA) accounted for the greatest proportion of accidental injury deaths across all ages (33%). Other important causes of injury death in younger children 1–4yrs were drowning (8%) fires/burns (7.2%), high falls (6.4%) and accidental strangulation (5.6%), while fires/burns (12.7%) and drowning (8.9%) accounted for a greater proportion of deaths in children 5–9yrs. Interpersonal violence accounted for at least 9.5% of all injury deaths and 1.6% of child mortality overall. The rate of injury fatalities in children 1–14yrs has declined by 40% over the period from 2007 to 2016; from an average of 4.2 deaths/100, 000 in 2007–2011 to 2.4 per 100, 000 in 2012–2016, due largely to a significant decline in RTA fatalities during this period. A male preponderance of deaths was apparent for all categories of injury particularly drowning (88%), accidental strangulation (75%) and falls (69%). Conclusions: Although welcome reductions in childhood mortality rates have been observed in Ireland in recent years, 26.5% of child deaths, attributable to accident and intentional injury are potentially avoidable and warrant further attention. National, age-specific data relating to the nature and circumstances of such deaths will assist in providing evidence based information with which to inform effective intervention strategies.